CD4+ T cells in ischemic stroke: effects and therapeutic targets - Lian, Zhengqi; Luo, Ying; Li, Yina; Gao, Yikun; Xiong, Xiaoxing; Gu, Lijuan (Frontiers in Immunology, 2025)
Ischemic stroke (IS) is a significant contributor to disability and death worldwide, with limited treatments beyond early intervention. The importance of CD4+ T cells in the advancement of IS has been highlighted by recent studies, providing new insights into immunomodulatory strategies. This review describes the spatiotemporal dynamics of CD4+ T cells and their subsets at different stages of IS. The signaling pathways activated by IS regulate the distribution of CD4+ T cells and their subsets, which further influences the inflammatory response and disease progression. In the acute and subacute stages, CD4+ T cells exacerbate neuronal damage. In contrast, CD4+ T cells, which are predominantly composed of Treg cells (Tregs), promote tissue repair and neurological recovery in the chronic stage. In light of recent findings that challenge traditional views, we analyze the underlying mechanisms and potential explanations for these discrepancies. In addition, we summarize the potential of targeting CD4+ T cells as a therapeutic strategy for IS. Although no drugs specifically targeting CD4+ T cells have been developed, certain drugs that modulate CD4+ T cells show potential for IS treatment. Moreover, multitarget drugs integrated with nanomaterials are currently undergoing preclinical investigation. We further explore the challenges in the clinical translation of CD4+ T-cell-targeted therapies and discuss potential strategies to address these challenges. In conclusion, a deeper comprehension of the complex effects of CD4+ T cells and their subsets on IS will contribute to disease management and drug development, thereby improving the quality of life for IS patients.